Routine justice: the intersection of race, gender and police discretion in traffic stops - Briggs, Jeremy S. (Kansas State University, 2013)
Racial profiling by the police on the nation’s streets and highways has attracted much attention over the past two decades from scholars, media figures, politicians and police administrators. Several highly publicized cases propelled the issue into national consciousness in the early and mid 1990s, bringing a new public awareness to an undoubtedly old problem. Despite the proliferation of research and political attention, many questions remain unanswered. Among the most common criticisms facing racial profiling research today is the literature's lack of theoretical development. Grounded in focal concerns theory and the concept of symbolic assailants, the present research draws upon both crime control and discriminatory frameworks of racial disparity in traffic stop outcomes. The findings suggest that, while police concerns of crime and safety diminish the effect of race/ethnicity and gender on stop outcomes, race and gender remain important predictors of police decisions. The implications are discussed.
Keywords: Racial profiling; Criminology (0627); Sociology (0626)